The Influence of Social Media Marketing on Purchase Intention and Brand Loyalty (Study on the Batik Fashion Customer in Pekalongan) - Hera Hayuda Pradani; Muchsin Muthohar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines the effect of brand trust, brand community, brand awareness, interaction, and emotional attachment on purchase intention and brand loyalty in the batik fashion industry in Pekalongan city. This study uses the purposive sampling technique. The primary data were collected from 240 respondents. This research uses Structural Equation Modeling (SEM) with SmartPLS software version 3.2.9 as a statistical analysis technique. The data analysis results indicate that brand trust, interaction, and emotional attachment positively and significantly influence purchase intention. In addition, purchase intention positively and significantly affects brand loyalty. However, brand community and brand awareness did not affect purchase intention.